A LoRa-Cloud Based Water pH and Air Temperature Sensor Hub: IoT Water Quality Monitoring Sensor Hub - Ly, Yap Sze; Hairom, Nur Hanis Hayati; Harun, Nor Hazlyna; Chin Fhong, Soon (Emerging Advances in Integrated Technology, 2022)
Water pollution has become one of the important issues in Malaysia which occurs frequently especially in the rivers of Selangor. One of the indicators of pollution is the pH of the water. Thus, the main purpose of this study was to design a LoRa-Cloud-based water pollution sensor hub to monitor the real-time water quality. Sensor devices for pH (SEN0161-V2), and temperature and humidity (DHT11) were used to accurately detect water pH, and air temperature and humidity, respectively. REYAX RYLR896 Long Range Low Power (LoRa) transceiver module enabled the transmission of sensor data from the sensor node to the gateway node, while NodeMCU ESP8266 enabled transmission of sensor data to the Cloud. Ubidots IoT platform was used to monitor the real-time sensor data. A 3 W power supply was continuously supplied to the prototype and autonomy was guaranteed with the addition of monocrystalline solar cells. The performance of the prototype device was tested based on the monitoring function, and the overall pH level of Taman Metropolitan Batu Park Lake was slightly alkaline as the pH of the lake water ranged from 7.32 to 9.08 with data updating every 5 minutes on the Ubidots dashboards. The LoRa-Cloud-based water pollution sensor hub was successfully developed to monitor the real-time water quality through the Ubidots IoT platform.